Tratamiento de la enfermedad arterial periférica de las extremidades inferiores con células mononucleares de médula ósea autólogas : reporte de seguimiento a un año (2012)
ABSTRACT: Autologous bone marrow mononuclear cells have been shown to be safe and effective for treatment of patients with peripheral arterial disease (PAD). Angiogenesis can also be induced by growth factors synthesized by them. Objective: To determine in Colombia the feasibility, safety and outcome of the afore-mentioned treatment. Methods: After informed consent, bone marrow was obtained by aspiration under local anesthesia; mononuclear cells were concentrated and their number and viability were established. They were suspended in saline solution and implanted by intramuscular injection into the gastrocnemius muscles of ischemic legs. Control patients were left untreated. Clinical evaluation included several parameters. Flow cytometry was used for cell analysis. Results: Mean age of patients: 69 ± 11 years; cell viability: 99.15 ± 0.76%; total number of injected cells: 9.2 x 108 ± 6.2 x 108 . After treatment, angiographic studies showed the formation of new collateral vessels in all patients, with minimal thickness increase. There were no complications from bone marrow aspiration and intramuscular administration of cells. All treated patients experienced increase in the walking distance and improvement of rest pain. Conclusions: These preliminary results demonstrate that autologous cell therapy is safe, feasible and positively changes the natural history of patients with advanced peripheral arterial disease. In order to establish this treatment as a current practice in Colombia, we suggest the study of a larger number of patients.